Affordability of family foods is associated with Nutritional Status of women with pre-school children in Addis Ababa, Ethiopia - Semira Abdelmenan; Alemayehu Worku; Hanna Y. Berhane; Yemane Berhane; Eva-Charlotte Ekström (Scientific Reports)
Abstract Malnutrition among women of reproductive age is a critical public health issue in LMICs, where undernutrition coexists with rising overweight and obesity rates. In Ethiopia, particularly among urban women, maternal and child undernutrition remains high despite efforts to combat poverty and food insecurity. This study examined the relationship between food affordability and the nutritional status of 4797 women in Addis Ababa. Using repeated cross-sectional surveys, body mass index was calculated, and women’s nutritional status was categorized. Data on the affordability of 11 healthy family food groups were collected and categorized into terciles. Multinomial logistic regression models analyzed the association between food affordability and nutritional status, adjusting for confounding factors. The prevalence of underweight among women was 7.3%, while 39.1% were overweight or obese. On average, families could afford 6.1 out of the 11 food groups. Women with higher food affordability had increased odds of being overweight (AOR: 1.32; 95% CI 1.09, 1.60) or obese (AOR: 1.50; 95% CI 1.14, 1.97). The findings highlight that two out of five women are either overweight or obese, with obesity more likely in those with greater perceived food affordability. Addressing food choices as food affordability improves is crucial, as better food affordability is associated with an increased risk of becoming overweight and obese.